Isometric force assessment and influence on the maximum velocity of swimmers of different levels - Marinho, P.; Orival, A. (Biomechanics and Medicine in Swimming IX, 2003)
The present study had as purpose to investigate the influence of the maximum isometric force (MIF) and the rate force development (RFD) on the performance of the swimmers velocity belonging to different levels of qualification. The result demonstrated a meaningful correlation only on G1. The lack of meaningful correlation on G2 may be associated with a higher influence exerted by the technique on the performance of these swimmers. The G3 being exclusively constituted of swimmers with low level of qualification presented the highest values of correlation, though not meaningful. In the presence of the results we can conclude that only in the group with heterogeneous level of qualification the isometric force exerted influence on the performance of the velocity.